2021
DOI: 10.1021/acschemneuro.1c00150
|View full text |Cite
|
Sign up to set email alerts
|

Multipronged Regulatory Functions of Serum Albumin in Early Stages of Amyloid-β Aggregation

Abstract: Human serum albumin (HSA) is a major interacting-partner of Alzheimer’s amyloid-β (Aβ) peptide in the plasma and has emerged as a promising therapeutic target. HSA inhibits Aβ fibrillization, but the underlying molecular mechanism is not well elucidated. In this work, we investigated the role of HSA in the early stages of Aβ aggregation by simulating the binding process of multiple Aβ monomers and protofibrils to HSA with extensive molecular dynamics simulations. HSA could simultaneously trap multiple Aβ monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Being a major carrier protein, HSA is one of the most potent Aβ sequestering agents, binding 90% to 95% of the Aβ in blood plasma [25]. Model organism studies indicated that serum albumin inhibits Aβ aggregation [26,27] and fibrillation [28][29][30] by binding Aβ monomers and oligomers, while human studies have revealed the association of low HSA levels with cognitive impairment [31,32] as well as AD [33,34]. A recent rather large study (n = 396) demonstrated that the HSA level is inversely associated as a continuous variable with Aβ deposition and Aβ positivity in older adults [35].…”
Section: Narrative 11 Contextual Backgroundmentioning
confidence: 99%
“…Being a major carrier protein, HSA is one of the most potent Aβ sequestering agents, binding 90% to 95% of the Aβ in blood plasma [25]. Model organism studies indicated that serum albumin inhibits Aβ aggregation [26,27] and fibrillation [28][29][30] by binding Aβ monomers and oligomers, while human studies have revealed the association of low HSA levels with cognitive impairment [31,32] as well as AD [33,34]. A recent rather large study (n = 396) demonstrated that the HSA level is inversely associated as a continuous variable with Aβ deposition and Aβ positivity in older adults [35].…”
Section: Narrative 11 Contextual Backgroundmentioning
confidence: 99%
“…Albumin, as a flexible hydrophobic protein, aggregates with amyloid‐forming proteins, prolonging the lag phase 22–24 . The unstable and soluble monomers present in the lag phase are able to integrate into the cell membrane and become more toxic 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Albumin is an abundant protein in the human body, flexible, and mostly hydrophobic; thus, it has a high nonspecific binding capacity 21 . It is known that albumin impedes the fibrillization of amyloids and increases the soluble misfolded oligomers of higher toxicity 22–24 . Akin to amyloid, co‐aggregation with albumin creates a soluble oligomeric form of [II] that is more toxic than its fibril form.…”
Section: Introductionmentioning
confidence: 99%
“…As elevated isoAsp levels in blood are associated with AD [8], an ELISA with 1A3 mAb could be used as an auxiliary tool in AD diagnostics. The fact that the targeted isoAsp residue resides in the HSA domain responsible for Aß binding and disrupting the structural transformation of Aß42 protofibrils to fibrils [28], potentially links deamidation at this site this to disease etiology. Although significant amount of preclinical and clinical research needs to be done for the assay validation, adding this analysis to already formidable arsenal of AD diagnostics tools will not incur much inconvenience and additional expense.…”
Section: Discussionmentioning
confidence: 99%
“…The 1A3 sensorgrams demonstrates a clear-cut concentration-response relationship with smooth and consistent curves indicative of good interactions (Figure 3a). The calculated K D value of 2.1 × 10 −8 M means an above-average (≈10 −6 M [28]) binding affinity.…”
Section: Kinetic Analysesmentioning
confidence: 93%